Relationship Between Plantar Tissue Hardness and Plantar Pressure Distributions in People With Diabetic Peripheral Neuropathy - Duan, Yijie; Ren, Weiyan; Liu, Wei; Li, Jianchao; Pu, Fang; Jan, Yih-Kuen (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: People with diabetic peripheral neuropathy (DPN) are usually accompanied with increased plantar pressure. Such high plantar loading during daily activities may cause changes in the biomechanical properties of plantar soft tissue, whose viability is critical to the development of foot ulcers. This study aimed to investigate the relationship between plantar tissue hardness and plantar pressure in people with and without DPN, and preliminarily explore the influence of plantar loading patterns on the plantar pressure and tissue hardness. Methods: The study was conducted on 14 people with DPN and 14 diabetic people without DPN. The Shore durometer and MatScan System were used to measure the plantar tissue hardness and plantar pressure, respectively. The plantar loading level was evaluated by the duration of daily weight-bearing activity and was used to group diabetic participants with and without DPN into two subgroups (lower loading group and higher loading group). Results: The plantar tissue hardness was significantly correlated with static peak plantar pressure (PPP, p<0.05) and dynamic pressure-time integral (PTI, p<0.05) in the forefoot region in people with DPN. Results of variance analysis showed a significant interaction effect between peripheral neuropathy and plantar loading on tissue hardness (p<0.05), but not plantar pressure. For people with DPN, significant differences in tissue hardness between the higher loading group and lower loading group were observed in the forefoot, midfoot and hindfoot regions. In the higher loading group, people with DPN had significantly greater tissue hardness than that in people without DPN in the toes, forefoot, midfoot and hindfoot regions (p<0.05). Conclusions: There is a significant correlation between tissue hardness and PPP, and between tissue hardness and PTI in people with DPN. Plantar loading associated with daily activities plays a significant role on the plantar tissue hardness in people with DPN. The findings of this study contribute to further understand the relationship between increased plantar tissue hardness and high plantar pressure in people with diabetic peripheral neuropathy.